Artificial Intelligence in Wealth Management: A Gradient Descent-Driven Framework for Intelligent Financial Decision-Making - Srinivasa Rao Gunda (International Journal of Computational and Experimental Science and Engineering, 2026)
Gradient descent optimisation has impacted the artificial intelligence movement, enabling the development of deep-learning systems in wealth management that process complicated financial datasets and challenges. It has been implemented with advanced neural network architectures such as LSTMs, CNNs, and deep belief networks for applications in portfolio optimisation, risk management, and personalisation to customers. The software infrastructure in modern wealth management is distributed computing systems with graphics processing unit acceleration and is designed to do real-time decision-making at scale on large portfolios of global assets and on heterogeneous flows of market data sources. Edge computing has been utilised for sub-millisecond inference latencies needed to forecast markets with real-time autonomous portfolio management in distributed computing. Adaptive forms of gradient descent have been used in the form of proximal gradient methods and explainable AI systems to overcome real-world constraints of transaction costs, regulation, and system explainability. In summary, this systematic assessment of gradual improvements in deep learning model architecture, optimisation algorithm efficiency, and system-level deployment has determined gradient descent to be the computational workhorse of the next-generation wealth management system. Future improvements through federated learning, reinforcement learning, and quantum computing will further enable adaptation in the changing financial industry.